Transcriptomic Response of Caenorhabditis Elegans Expressing Human Aß42Gene Treated with Salvianolic Acid A - Chee, Wah Yuen; Mardani Abdul Halim; Nazalan Najimudin; Ghows Azzam (Indian Academy of Sciences, 2021)
Alzheimer’s disease is associated with the deposition of ß-amyloid peptide in the brain. A genome-wide transcriptomic study was performed to determine the response of transgenic Caenorhabditis elegans expressing full-length human Aß42 gene towards salvianolic acid A (Sal A). The genes associated with antioxidant response, gst-4, gst-10, spr-1 and trxr-2, were upregulated. Aß42 caused oxidative stress and the antioxidant response genes possibly provide some sort of protection to the nematode. trxr-2 gene product was also associated with the defence system and probably has a role in the lifespan of the nematode. Other genes involved in DNA replication, reproduction, immune response and antimicrobial activities were also found to be upregulated. Treatment of Sal A also increased the rate of reproduction in the nematode, and elevated its immunological protection system towards microorganisms. On the other hand, the genes responsible for ligand-gated cation channel, embryonic and postembryonic development, locomotion and neuromodulation of chemosensory neurons were found to be downregulated. As an effector, Sal A might conceivably reduce the movement of the nematode by interfering with neuronal transmission, and embryonic and postembryonic development.